PENGARUH ETIKA, KOMITMEN ORGANISASI DAN PENEKANAN ANGGARAN TERHADAP BUDGETARY SLACK (STUDI PADA OPD KAB. KEPAHIANG) - Eduar Widyantoro; Nensi yuniarti Zs; Yudi Partama Putra; Ahmad Junaidi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This study aimed to determine the effect of ethics, organizational commitment and budget emphasis on budgetary slack. The population of this study was the SKPD in Kepahiang Regency which consists of 9 Agencies or Services in Kepahiang Regency. This study used descriptive quantitative research method. The sample of this study was selected by using a purposive sampling technique. The data wre collected by using a questionnaire. The data were analyzed by using validity tests, reliability tests, hypothesis testing and multiple linear regression analysis with SPSS version 22.0 software. The results of this study indicate that Ethics partially has effect on budgetary slack in SKPD. This was proved by the t test results showing the t_sig value for the Ethics variable, namely sig a = 0.000 < 0.05 with a t table value of 5.908. The organizational commitment partially has effect on budgetary slack. This is proved by the t test results showing the t_sig value for the organizational commitment variable, namely sig a = 0.000 < 0.05 with a t table value of 8.928. Budget emphasis partially has effect on budgetary slack. This was proved by the t test results showing the t_sig value for the organizational commitment variable, namely sig a = 0.010 < 0.05 with a t table value of 2.644. Ethics, organizational commitment and budget emphasis simultaneously have a significant effects on budgetary slack in SKPD. This was proved by the results of the F test which shows a sig value of less than 0.05, 0.000.  Keywords: Ethics, Organizational Commitment, Budget Emphasis and Budgetary Slack.